2010
DOI: 10.1007/s10750-010-0351-3
|View full text |Cite
|
Sign up to set email alerts
|

Out of Alaska: morphological diversity within the genus Eurytemora from its ancestral Alaskan range (Crustacea, Copepoda)

Abstract: The copepod genus Eurytemora occupies a wide range of habitat types throughout the Northern Hemisphere, with among the broadest salinity ranges of any known copepod. The epicenter of diversity for this genus lies along coastal Alaska, where several species are endemic. Systematic analysis has been difficult, however, because of a tendency toward morphological stasis in this genus, despite large genetic divergences among populations and species. The goals of this study were to (1) analyze patterns of morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 38 publications
3
5
0
3
Order By: Relevance
“…The idea that each predator has at least twice the mass (or 1.26 the linear dimensions) of its prey, and that a ratio of sizes varying from 1.1 to 1.4 (with the mean ratio being roughly 1.3) is necessary to permit two species to co-occur in different niches but at the same level of a food web, are further hypotheses contained in the ''Homage.' ' Dodson et al (2010) found this latter ratio consistent with their observations on co-occurring Eurytemora species. However, taking into account that observations of body size from fieldcaught samples cannot reveal whether body size displacement is the result of phenotypic plasticity or selection, the authors underline that body size displacement according to Hutchinson's hypothesis would be a consequence of natural selection acting to reduce competition between species.…”
Section: From Phytoplankton To Zooplankton: How Biotic Interactions Asupporting
confidence: 90%
See 1 more Smart Citation
“…The idea that each predator has at least twice the mass (or 1.26 the linear dimensions) of its prey, and that a ratio of sizes varying from 1.1 to 1.4 (with the mean ratio being roughly 1.3) is necessary to permit two species to co-occur in different niches but at the same level of a food web, are further hypotheses contained in the ''Homage.' ' Dodson et al (2010) found this latter ratio consistent with their observations on co-occurring Eurytemora species. However, taking into account that observations of body size from fieldcaught samples cannot reveal whether body size displacement is the result of phenotypic plasticity or selection, the authors underline that body size displacement according to Hutchinson's hypothesis would be a consequence of natural selection acting to reduce competition between species.…”
Section: From Phytoplankton To Zooplankton: How Biotic Interactions Asupporting
confidence: 90%
“…The importance of niche diversity and allopatric speciation (eventually followed by secondary recolonization) for generating species diversity, as expressed by Hutchinson, is the driving hypothesis in the article by Dodson et al (2010) to explain the morphological diversity within the eurihaline genus Eurytemora from its ancestral Alaskan range. The idea that each predator has at least twice the mass (or 1.26 the linear dimensions) of its prey, and that a ratio of sizes varying from 1.1 to 1.4 (with the mean ratio being roughly 1.3) is necessary to permit two species to co-occur in different niches but at the same level of a food web, are further hypotheses contained in the ''Homage.'…”
Section: From Phytoplankton To Zooplankton: How Biotic Interactions Amentioning
confidence: 99%
“…Tolerance to abiotic factors may facilitate dispersal success (Dodson et al, 2010;Hirsch et al, 2016), suggesting that tolerance to cyanobacteria could also promote the invasion of Eurytemora to new ecosystems, as seen in Lake Michigan. Lee et al (2013) showed that high food availability and tolerance to lower salinity also promote invasions by Eurytemora to new systems.…”
Section: Resultsmentioning
confidence: 99%
“…It was later reported in Lake Michigan by Robertson (1966), and since the late 1960s the species is found in both littoral areas and pelagic plankton communities in Green Bay (Gannon, 1974). The species complex has spread multiple times independently from brackish water to freshwater, and established clades in different parts of the world due to its ability to adapt locally (Dodson et al, 2010). There are at least six recognized clades of E. affinis; one clade in Asia, one in Europe, and four in America (Lee, 2000), with recent studies indicating that North American clades represent a separate species (E. carolleeae; Alekseev and Souissi, 2011;Vasquez et al, 2016).…”
Section: Study Speciesmentioning
confidence: 99%
“…The genus has hitherto been recorded exclusively from subtropical to subarctic, but with the increasing species diversity toward northern latitudes (Dodson et al 2010). Most of the Eurytemora are characterized by a wide habitat distribution ranging from the open ocean waters, coastal marine, hypersaline salt marshes, and brackish estuaries, to completely freshwaters (Heron and Damkaer 1976;Lee 2000;Dodson et al 2010).…”
Section: Introductionmentioning
confidence: 99%